A quiet life : a novel - Joella, Ethan (Scribner, 2022)
From the author of A Little Hope--a Read with Jenna Bonus Pick--comes an enormously powerful and life-affirming novel about three individuals whose lives intersect in unforeseen ways. Set in a close-knit Pennsylvania suburb in the grip of winter, A Quiet Life follows three people grappling with loss and finding a tender wisdom in their grief. Chuck Ayers used to look forward to nothing so much as his annual trip to Hilton Head with his wife, Cat--that yearly taste of relaxation they'd become accustomed to in retirement, after a lifetime of working and raising two children. Now, just months after Cat's death, Chuck finds that he can't let go of her things--her favorite towel, the sketchbooks in her desk drawer--as he struggles to pack for a trip he can't imagine taking without her. Ella Burke delivers morning newspapers and works at a bridal shop to fill her days while she anxiously awaits news--any piece of information--about her missing daughter. Ella adjusts to life in a new apartment and answers every call on her phone, hoping her daughter will reach out one day. After the sudden death of her father, Kirsten Bonato set aside her veterinary school aspirations, finding comfort in the steady routine of working at an animal shelter. But as time passes, old dreams and new romantic interests begin to surface--and Kirsten finds herself at another crossroads. In this beautifully crafted and profoundly moving novel, three parallel narratives converge in poignant and unexpected ways, as each character bravely presses onward, trying to recover something they have lost. Emotionally riveting and infused with hope, A Quiet Life celebrates humanity in the midst of uncertainty.